Current concepts of regenerative biomaterials in implant dentistry - Annapurna Ahuja; Vipin Ahuja; Kumar Saurav Singh (Wolters Kluwer Medknow Publications, 2015)
The primary objective of any implant system is to achieve firm fixation to the bone and this could be influenced by biomechanical as well as biomaterial selection. An array of materials is used in the replacement of missing teeth through implantation. The appropriate selection of biomaterials directly influences the clinical success and longevity of implants. Thus the clinician needs to have adequate knowledge of the various biomaterials and their properties for their judicious selection and application in his/her clinical practice. The recent materials such as bioceramics and composite biomaterials that are under consideration and investigation have a promising future. For optimal performance, implant biomaterials should have suitable mechanical strength, biocompatibility, and structural biostability in the physiological environment. This article reviews the various implant biomaterials and their ease of use in implant dentistry.